2013
DOI: 10.1007/s11033-012-2278-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-153 is tumor suppressive in glioblastoma stem cells

Abstract: Glioblastoma multiforme (GBM) is lethal brain tumor thought to arise from GBM stem cells (GBM-SCs). MicroRNAs carry out post-transcriptional regulation of various cellular processes that modulate the stemness properties of GBM-SCs. Here, we investigated the critical role of miR-153 in GBM-SCs. First, GBM-SCs were isolated from six GBM specimens. These GBM-SCs formed GBM spheres, expressed markers associated with neural stem cells, and possessed the capacity for self-renewal and multilineage differentiation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 32 publications
3
37
0
1
Order By: Relevance
“…Furthermore, antiapoptotic protein Bcl-2 and induced myeloid leukemia cell differentiation protein (Mcl-1) were downregulated by miR-153 upregulation. Zhao et al (2013) discovered that transient transfection of miR-153 in glioblastoma stem cells induces apoptosis. Furthermore, low expression level of miR-153 was found to be significantly related to metastasis and poor prognosis in oral cancer patients by targeting SNAI1 and ZEB2 (Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antiapoptotic protein Bcl-2 and induced myeloid leukemia cell differentiation protein (Mcl-1) were downregulated by miR-153 upregulation. Zhao et al (2013) discovered that transient transfection of miR-153 in glioblastoma stem cells induces apoptosis. Furthermore, low expression level of miR-153 was found to be significantly related to metastasis and poor prognosis in oral cancer patients by targeting SNAI1 and ZEB2 (Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted using various human prostate cancer cell lines demonstrate miR-153 represses PTEN expression to activate AKT kinase and downregulate the transcriptional activity of Forkhead box O (FOXO)1, leading to upregulation of the G1/S transitional promoter cyclin D1 and downregulation of the cyclin-dependent kinase (CDK) inhibitor p21 [98]. In contrast, miR-153 levels are shown to be reduced in human glioblastoma multiforme [99]. miR-153 induces apoptosis in these tumors by targeting Bcl-2 and Mcl-1, suggesting that miR-153 functions as a tumor suppressor [100].…”
Section: Mir153-1/2mentioning
confidence: 99%
“…miR-153 induces apoptosis in these tumors by targeting Bcl-2 and Mcl-1, suggesting that miR-153 functions as a tumor suppressor [100]. Studies have revealed a tendency toward downregulation of miR-153 in relation to lymph node metastasis in ovarian epithelial tumors [101], and downregulation of miR-153 in high-risk medulloblastomas [99]. Therefore, miR-153 may function as a tumor suppressor or an oncogene depending on the tissue.…”
Section: Mir153-1/2mentioning
confidence: 99%
“…A miRNS-ek szerepe napjainkban talán leginkább a daganatpatológiában kap a legtöbb figyelmet, hiszen ezek a kis molekulák a gének poszttranszkripcionális szabályozása révén hozzájárulnak a daganatos szövet kialakulásához, növekedéséhez és tovaterjedéséhez is, így egyes esetekben akár biomarkerként is felhasználhatóak lehetnek [25,26]. Klinikai alkalmazásuk reményében a miRNS-ek szintjét manapság már szinte kivétel nélkül minden daganattípus-ban kiterjedten vizsgálják: tüdődaganatokban [27,28], emlőtumorokban [29,30], a vastagbél, a prosztata és a máj rosszindulatú [31,32,33] elváltozásaiban, de ritkábban előforduló tumorok esetében is, így agyda-ganatokban [34] vagy a mellékvesekéregből kiinduló rosszindulatú folyamatokban is [35].…”
Section: Megbeszélésunclassified